SPECTROPHOTOMETRIC DETERMINATION OF ASCORBIC ACID BY HORSERADISH PEROXIDASE - Đurić, Vladan R.; Deletić, Nebojša R. (Bulletin of Natural Sciences Research, 2020)
L-ascorbic acid is one of the essential nutrients and most common food supplements, fortificants, and preservatives. It is commercially available as solutions, drops, tablets, capsules, crystal powder, beverage mixtures, multivitamin formulations, and multi antioxidant formulations. The usual daily dose is from 25 mg to 1.5 g. Ascorbic acid is a distinctly reducing agent with low redox potential (0.18 and 0.08 V at pH 4.5 and 6.4, respectively). Based on ascorbate property, numerous methods for its quantitative determination are developed, from titrimetric, electrochemical, and chromatographic methods, to fluorometric and kinetic ones. Enzyme peroxidase is interfered with by ascorbic acid, which decreases the oxidation speed of its co-substrates during hydrogen peroxide decomposition by peroxidase. Absorbance changes at the wavelength of corresponding reagents are in correlation with ascorbate concentration. During this study, benzidine and o-tolidine have been used as chromogenic reagents. Reaction conditions were optimized for various buffer systems, calibration curves were constructed, and limits of detection (0.04 μmol/L) and quantification (0.12 μmol/L) were calculated. Using calibration charts, it was possible to detect ascorbic acid within limits from 0.4 to 10 μmol/L. The optimized method was applied for the determination of ascorbic acid in pharmaceutical products. The method was characterized by exceptional sensitivity and accuracy, but only for preparations not containing substances that affect enzyme peroxidase.
Keywords: L-ascorbic acid; Peroxidase; Spectrophotometry